Popular culture genres : theories and texts, Vol. 2 - Berger, Arthur Asa, 1933- (Newbury Park : Sage Publications, 1992)
Popular Culture Genres is distinctive because it begins a fresh, elaborate discussion of a cultural phenomenon--the genre--in a concise and readable style. While much of the current scholarship surrounding popular culture is highly theoretical and largely abstract, Arthur Asa Berger offers a witty, accessible study of genres and genre criticism, which, based on the methods and examples he provides, empowers readers to make their own analyses. Part I deals with genres from a critical perspective, asking such questions as: how do the conventions of different genres affect the creation and production of texts and the audiences of these texts? Do certain genres have significant social and political implications? How do genres evolve? And why do some genres (such as the Western) die out? Part II takes a look at five "classic" popular texts (in both their novel and film versions): The Maltese Falcon (tough-guy detective), Murder on the Orient Express (classic detective), Dr.
No (spy story), War of the Worlds (science fiction), and Frankenstein (horror). Viewing these works in the context of their respective genres is not only instructive but fascinating reading as well.
Pt. I. Theories. 1. On the Structure of Genres. 2. Propp, de Saussure, and the Narrative. 3. Formulas and Texts. 4. Genre Theory. 5. Genre, Society, and Culture. 6. The Classic Mystery: A Case Study -- Pt. II. Texts. 7. Murder on the Orient Express. 8. The Maltese Falcon: The Hard-Boiled Detective Novel. 9. Dr. No. 10. War of the Worlds. 11. Frankenstein: The New Prometheus. 12. Conclusions.
Includes bibliographical references (p. 160-162) and indexes.
Keywords: Mass media; Popular culture; Literary form